The Influence Of Perceived Quality Of Teaching, Student Life And Support, Social Identification And Interaction On Student Satisfaction On Intention To Stay At The Islamic University Of Indonesia - Muhammad Farruqi Al-Islami; Arif Hartono (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to analyze the influence of Perceived Quality of Teaching, Student Life and Support, Social Identification, and Interaction on Student Satisfaction and Intention to Stay at the Indonesian Islamic University (UII). Quantitative research methodology is applied. 164 respondents from the Islamic University of Indonesia's class of 2023 were included in this study. Data was gathered via a Google Form-based online survey, and SPSS and PLS-SEM with SmartPLS software were used for analysis. According to the study's findings, social interaction and identification positively and significantly affect students' levels of satisfaction. On the other hand, there was no significant positive correlation found between student satisfaction and perceived quality of teaching, student life, and student support. In addition, this study shows that intentions to stay are positively impacted by student satisfaction. Additionally, this study recommends that marketing managers concentrate on enhancing the elements that contribute to students' satisfaction with their university experience.